Towards field trace metal speciation using electroanalytical techniques and tangential ultrafiltration - Monteiro, Adnívia Santos Costa [UNESP]; Parat, Corinne; Rosa, André Henrique [UNESP]; Pinheiro, José Paulo (Elsevier, 2016)
In this work we propose a trace metal speciation methodology to determine the total, free and ultrafiltered (<1 KDa) metal fractions using electrochemical methods (SCP and AGNES) and tangential ultrafiltration (UF) experiments that can easily be carried out on-site. We tested our methodology spiking Cadmium ions into two natural waters samples from Itapanhau and Sorocabinha rivers in Sao Paulo State, Brazil. The limits of detection (LOD) was 1.6×10-9 M for the total Cd2+ determination performed by Stripping Chronopotentiometry (SCP) in the source and acidified ultrafiltered solution and 1.9×10-9 M for the free Cd2+ determination using Absence of gradients and Nernstian equilibrium stripping (AGNES), using a thin mercury film electrode. The total metal determination was performed by SCP in acidified samples and the results compared with graphite furnace atomic absorption spectroscopy (GF-AAS). The SCP results were adequate with a 96% of recovery from the known metal spike for the 12 samples tested. For the Itapanhau sample the free metal determined by AGNES and the ultrafiltered fraction are identical, while for the Sorocabinha the free metal in the source is significantly smaller than the ultrafiltered fraction, indicating that this sample must be rich in metal complexes with small inorganic ligands that are able to permeate the 1 kDa membrane. The proposed metal speciation methodology validated in the laboratory combining UF and SCP/AGNES is able to be used in on-site experiments providing valid information regarding the total and free metal concentrations and additionally some insight on the role of small inorganic ligands to the metal complexation.
Keywords: AGNES; Cadmium; On-site analysis; Stripping chronopotentiometry; Tangential ultrafiltration; Trace metal speciation